Indigenous plants and tuber as alternative food sources for Temiar communities during flood situations - Mohammad Amizi Ayob; Aminah Nutman; Lee, Lih Huey; Anidah Alias; Shamsul Khamis; Nur Eleena Farihin Redzuan Hafiz Boon; Tew, Sue Teng; Soon, Jan Mei (AENSI Publisher, 2016)
Temiar tribal people are famous for using forest resources as their food and medicinal supply. During the 2004 monsoon flood, affected villagers evacuated to nearby hills to escape the flood and rising river water. Hence, Temiar communities who rised to practise the utilization of indigenous plants and tubers were forced to search for alternative food sources during the flood. Hence it is the objective of this paper to determine the types of indigenous plants and tubers used as food sources by the affected villagers. Sampling of plants consumed by the villagers were conducted at selected villagers. Voucher specimens were created and sent for identification. Fourteen types of plants and tuber were identified as alternative food sources by the Temiar communities used during the natural disaster. Plant species include paddy (Oryza glaberrima), tuber (Manihot esculenta), shrubs (Solanum torvum, Clidemia hirta), palm (Arenga obtusifolia), herbaceous (Erechtites valerianifolia, Eryngium foetidum, Pentaphragma begoniifolium), macrofungus (Auricularia sp.) bamboo shoot (Dendrocalamus asper), wild fruits (Castanopsis megacarpa, Molineria capitulata and Rubussumatranus) and water extracted from stem of Caesalpiniasappan. Wild local plants were readily available and contributed nutrients and energy to the villagers.The identification of 14 types of food plantsand tuber will provide alternative food sources for the Temiar ethnic groups particularly during lack of food availability and accessibility.